34.7k views
4 votes
Can anyone help?....

Can anyone help?....-example-1
User CragMonkey
by
5.9k points

2 Answers

5 votes

Answer:
fg(x)=4x^3+12x^2-5x-15

Explanation:

Given:
f(x)=4x^2-5\text{ and } g(x)=x+3

We know that for any function f(x) and g(x), the multiplication function (fg) (x) is given by :-


fg(x)=f(x)g(x)

Now, for the given functions, we have


fg(x)=(4x^2-5)(x+3)\\\\\Rightarrow\ fg(x)=4x^2(x+3)-5(x+3)\\\\\Rightarrow\ fg(x)=4x^3+12x^2-5x-15

User Ofer
by
5.1k points
3 votes
The answer two this question is C.

You can get this answer by multiplying the two polynomials and then simplifying. See the steps below:
(4x^2 - 5)(x + 3) ---> Now multiply the two parenthesis.
4x^3 - 5x + 12x^2 - 15 ---> Arrange the numbers by decreasing exponents.
4x^3 + 12x^2 - 5x - 15

No simplifying can be done since there are no like terms.
User Manolis Karamanis
by
5.8k points